Study of B¯d,s⁎0→Dd,s+M- Decays with QCD Factorization Approach - Qin Chang; Xiaohui Hu; Zhe Chang; Junfeng Sun; Yueling Yang (Advances in High Energy Physics)
Motivated by the b-physics experiments at running LHC and upcoming SuperKEKB/Belle-II, the nonleptonic B¯q⁎0→Dq+M- (q=d,s and M=π,K,ρ,K⁎) weak decays are studied within QCD factorization framework. The observables of these decay modes are first predicted. It is found that the tree-dominated and CKM-favored B¯q⁎0→Dq+ρ- decays have the largest branching fractions ~O(10-8) and thus are hopefully to be measured. The B¯q⁎0→Dq+V- decays are dominated by the longitudinal polarization states. In addition, associating with the relevant B meson decays, some interesting phenomena and relations are discussed in detail; for example, RB≡B(B¯q→Dq⁎P)/B(B¯q⁎→DqP)≃3τB/τB⁎, and fL,∥(B¯q→Dq⁎V)≃fL,∥(B¯q⁎→DqV).